REPRESENTING GEOSCIENTIFIC KNOWLEDGE IN CYBERINFRASTRUCTURE: SOME CHALLENGES, APPROACHES, AND IMPLEMENTATIONS - Brodaric B.; Gahegan M. (My University, 2006)
Networks of databases and tools are being constructed in the geosciences to facilitate geoscientific computing and to stimulate new research. These efforts are contributing to an emerging geoscientific cyberinfrastructure that has the potential to be an important new operational paradigm for the geosciences. However, limited research has been undertaken on the adaptation of emerging cybertechnology to geoscience knowledge and practice. Consequently, we examine the nature of geoscientific knowledge and practice and identify a series of challenges related to representing and using these in emerging computational networks. The first main challenge emphasizes enhanced representation of geoscientific knowledge via ontology development, and the second calls for enhanced tools for processing the knowledge within database networks. We also briefly restate a schema that addresses several of the representation challenges and outline its implementation by different government agencies in three database networks. The identification of challenges, their treatment in the schema, and the implementations all contribute in part to the conceptualization and realization of a cyberinfrastructure for the geosciences. © 2006 Geological Society of America. All rights reserved.
Keywords: CYBERINFRASTRUCTURE; GEOSCIENCE KNOWLEDGE; GEOSCIENCE REASONING; KNOWLEDGE REPRESENTATION; ONTOLOGY